Starlink Satellite Project in A Developing Country - Vivek Reddy Gadipally (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
SpaceX and Elon Musk are leading a long-term initiative called Starlink to solve inequities in rural broadband Internet access.In order to provide constant, high-speed Internet access worldwide, the project aims to launch thousands of smallsat-class satellites into low Earth orbit (LEO) as a component of a mega constellation. SpaceX thinks that by utilizing shallow orbits, their technology may surpass the competition. Starlink assures its clients of reduced latency and improved connection quality in contrast to conventional geosynchronous satellite Internet infrastructure (Walker & Elliott, 2021). The purpose of this study is to look at how the Thai public views the Starlink satellite project. An online survey was employed to gather data from a convenience sample of 1,258 people in Thailand, using a quantitative methodology. To analyze the data, binary regression analysis was done. The results showed that factors such as gender, age, computer, laptop, tablet, wearable device, length of Internet use, mobile Internet, Instagram, TikTok, and YouTube could all be used to characterize how the public in Thailand felt about the Starlink Satellite project.The major reason is Starlink needs to come up with a clever plan to encourage customers to adopt satellite Internet in nations where fiber Internet is more readily available and reasonably priced.